STUDENTS’ INTRODUCTORY PARAGRAPH IN WRITING ACADEMIC ESSAY - Eka Dyah Puspita Sari; Mia Fitria Agustina (STKIP Siliwangi, 2022)
There are three structures of academic essay: introductory, body, and concluding paragraphs. This research puts its focus on the introductory paragraph. The objective of this research is to analyze students’ introductory paragraph in writing academic essay in forms of the analysis of the general statements and thesis statement. This research was qualitative research and the data was collected from students’ writing. The respondents of this research were third semester students of English literature study program. The result of the analysis shows that most of the students’ essay (90,7%) put general statements on introductory paragraph. It shows good result in practice because students already know the importance of general statements in introductory paragraph. Students comprehend and implement the main function of general statements, i.e. to attract the reader’s attention. In addition, it was also revealed that there were 68,5% of the students’ essay put thesis statement on introductory paragraph. The result is quite satisfying, although there are some of the essays not contain thesis statement. Indeed, thesis statement is important in writing introductory paragraph because it functions to state the specific subdivisions of the topic and/or the “plan” of the paper.